A WTO-compatible border tax adjustment for the ETS to finance the EU budget - Alexander Krenek; Mark Sommer; Margit Schratzenstaller (Austrian Institute of Economic Research (WIFO), 2020)
One element of the proposed European Green Deal is a border carbon adjustment mechanism. The introduction of a BCA would allow the EU to phase out current carbon leakage provisions of the ETS and to auction off all emission allowances, thus rendering the ETS a more effective unilateral tool to price and reduce carbon emissions. In theory a BCA would be a perfect instrument to ensure a level playing field for domestic and foreign producers, thus avoiding potential carbon leakage. Until now, however, the legal and administrative issues of implementation have been deemed too huge to overcome. We derive a WTO-compatible (full) border tax adjustment (BTA) design that could be implemented in the near future, and we estimate potential EU BCA and BTA revenues using a dynamic new Keynesian (DYNK) model. The BTA design of our choice would generate substantial and stable revenues that could be used as innovative sustainability-oriented own resource to finance the EU budget. We find that estimated revenues would suffice to finance between 5 and 7 percent of the EU's expenditure in the coming Multiannual Financial Framework period 2021-2027 and up to 16 percent in the year 2050. This new revenue source would allow member states to reduce their current contributions to the EU budget accordingly and would thus create space to cut other more distortionary taxes at the national level, enabling an EU-wide supranational sustainability-enhancing tax shift. Thus, a BTA could contribute to tackle both environmental and fiscal challenges currently facing the EU.
Keywords: F02; F36; F47; F53; H23; H87; 330; EU budget; sustainability-oriented taxation; border carbon adjustment; border taxadjustment; EU revenue system; EU own resources; emission trading system; carbon pricing